Elaboración de yogurt natural a base de hongos (kéfir) - Morocho Nivelo Carlos Enrique (Machala: Universidad Técnica de Machala, 2022)
The objective of the present investigation is to present this project on the elaboration of natural yogurt based on mushrooms (kefir) and vitamins, for the consumption of people who suffer from digestive problems or who want to prevent them since there are many benefits when consuming it and the contributions beneficial to our body, thus establishing a natural way of eating and making people aware of the damage that can cause our body to consume products made from chemicals. To maintain good health it is essential to choose food well, drink plenty of water, eat fruits, and eat natural products free of chemicals. Studies recently carried out in Ecuador show that most of the population have inadequate diets, resulting in a high percentage of diseases, companies and companies of processed products have a great preponderance when helping to reduce said problem. that is affecting the population in general due to the consumption of unhealthy foods, this problem isolates to improve the quality of life of the population, which tries to favor the aspects of individuals in all areas, especially in health, to achieve a balance of vitality and dignity in everyday life. The idea of this project on the elaboration of natural yogurt based on mushrooms (kefir) due to the fact that there are many people who today consume yogurt prepared with chemical bases, which causes great discomfort every day, such as cancer or acid to the stomach, for which we realized that it was possible to make a natural yogurt based on kefir mushrooms since this kefir mushroom is rich in vitamins, especially calcium, magnesium and phosphorus. Our product is made from two main ingredients, which are: milk, which is a food rich in calcium, and kefir, which is a microorganism that provides many health benefits. These products are 100% natural and combined, they provide benefits from the start. strengthening of the immune system to external levels such as the improvement of acne problems or scars, we can emphasize the relief of digestive problems, osteoporosis, bacterial infections, asthma and allergies, lactose intolerance, and the most devastating thing that is Cancer . For the materialization of this project, eating habits and the consumption of yogurt were studied, for which a quantitative methodology was used, with a structured survey model for adult women and men, youth, adolescents and children of our city, with a sample of 194 people. It was possible to collect information on the monthly consumption of yogurt in people in the city of Machala, revealing the results that a large number of people consume yogurt monthly and the ignorance of people about natural yogurt based on Kefir mushroom, it was also possible to observe the great acceptance that this natural yogurt would have in the market. Using the Canva business model, the marketing channels for our product, relationship with customers, source of income, assets for business operation, business activities, partner network, cost structure were analyzed. This valuable information obtained may remain as a basis for future research.
El objetivo de la presente investigación es presentar este proyecto sobre la elaboración de yogurt natural a base de hongos (kéfir) y vitaminas, para el consumo de personas que padecen problemas digestivos o que quieren prevenirlos ya que son muchos los beneficios al consumirlo y los aportes beneficiosos a nuestro organismo, estableciendo asi una manera de alimentación natural y concientizando a las personas sobre el daño que puede causar a nuestro organismo consumir productos elaborados a base de químicos. Para conservar una buena salud es esencial elegir bien los alimentos tomar mucha agua, comer frutas, ingerir productos naturales libres de químicos. Estudios realizados recientemente en el Ecuador dan como resultado que la mayor parte de la población tienen modos de alimentación no adecuados dando como resultado un alto porcentaje de enfermedades, las empresas y compañías de elaborados tienen gran preponderancia al momento de ayudar a la disminución de dicho problema que está afectando a la población en general por consumo de comidas poco saludables, este problema aísla a mejorar la calidad de vida de la población, lo cual trata de favorecer los aspectos de los individuos en todos los ámbitos, especialmente en la salud, para lograr un equilibrio de vitalidad y dignidad en el día a día. La idea de este proyecto sobre la elaboración de yogurt natural a base de hongos (kéfir) debido que existen muchas personas que hoy en día consumen yogurt preparados a bases de químicos lo que provoca al consumirlo, día a día grandes molestias como son el cáncer o acides al estómago, por lo cual nos dimos cuenta que era posible elaborar un yogur natural a base de hongos kéfir ya que este hongo kéfir es rico en vitaminas como son especialmente el calcio, magnesio y fosforo. Nuestro producto es elaborado por dos ingredientes principales que son: la leche que es un alimento rico en calcio, y el kéfir que es un microorganismo que aporta con gran muchos beneficios a la salud, estos productos son 100% naturales y fusionados brindan beneficios desde el reforzamiento del sistema inmunológico hasta niveles externos como la mejora de problemas de acné o cicatrices, podemos recalcar sobre el alivio a los problemas digestivos, osteoporosis, infecciones bacterianas, asma y alergia, la intolerancia a la lactosa, y lo más devastador que es el Cáncer. Para la materialización de este proyecto se estudió hábito alimenticio y el consumo de yogurt, por lo que se empleó una metodología cuantitativa, con un modelo de encuesta estructurada a mujeres y hombres adultos, jóvenes, adolescentes y niños de nuestra ciudad, con una muestra de 194 personas. Se logró recolectar información sobre el consumo mensual de yogurt en las personas en la ciudad de Machala, revelando los resultados que gran cantidad de personas consume yogurt mensualmente y el desconocimiento de las personas acerca de yogurt natural a base hongo Kéfir, también se pudo observar la gran aceptación que tendría en el mercado este yogurt natural. Mediante el modelo de negocios Canva se analizó los canales de comercialización para nuestro producto, relación con los clientes, fuente de ingresos, activos para el funcionamiento del negocio, actividades del negocio, red de socios, estructura de costos. Esta valiosa información obtenida puede quedar como base para futuras investigaciones.
Keywords: YOGURT; KÉFIR; SALUD; NATURAL